Cyberbullying as actionable tort (2022)
Bullying has always been a problem. But with the advent of cyberspace and the concomitant rise of "cancel culture," its already harmful effects have since increased exponentially in the form of cyberbullying. Now, anyone and everyone can fall victim to hateful words online. While bullying has been glossed over by society for the longest time, the 21st century's renewed emphasis on mental health necessitates a careful examination of this phenomenon and its legal consequences for both the victim and the perpetrator. In line with that, this Article posits that cyberbullying constitutes an actionable tort under the Civil Code from which aggrieved persons can seek relief. This Article also provides an argumentative framework for litigating tortious cyberbullying actions before the courts.
Keywords: Cyberbullying; Torts; Actions and defenses (Law); Actions on the case